Edaravone for acute stroke: Meta-analyses of data from randomized controlled trials. (3rd September 2015) - Yang, Jie; Cui, Xiaoyang; Li, Jie; Zhang, Canfei; Zhang, Jing; Liu, Ming
Abstract: Aims : To assess the effectiveness of edaravone for acute stroke including ischemic stroke and intracerebral hemorrhage (ICH). Methods : We identified randomized controlled trials with comprehensive searches and performed systematic reviews according to the Cochrane methods of systematical reviews. Results : Edaravone can reduce the rate of death or long-term disability significantly for acute ischemic stroke (AIS) (RR = 0.65; 95%CI, 0.48 to 0.89, p = 0.007). However, sensitivity analysis yielded a different result. Edaravone can also improve the short-term neurological impairment of AIS (MD = 7.09; 95%CI, 5.12 to 9.05, p < 0.00001), and ICH (MD = −4.32; 95%CI, −5.35 to −3.29, p < 0.00001). Conclusions : Edaravone is beneficial in improving neurological impairment resulting from AIS and ICH. However, currently there is no enough convincing evidence that edaravone reduces death or long-term disability for AIS and ICH.